PENDIDIKAN ISLAM DI KANADA - Najib Amrullah (CV. ADIBA AISHA AMIRA, 2021)
The entry of Islam in Canada is inseparable from Muslim immigrants who began in 1880 AD, so that Islamic education was formed. Islamic education in Canada is realized in educational institutions that were established as centers of Islamic studies, there are at least 20 Islamic educational institutions in the form of Islamic schools and several Islamic universities and public universities that open Islamic studies study programs. Canada is a major destination in education because education in this country includes one of the best quality levels of education in the world. Canada ranks highly globally such as the Global Peace Index and the United Nations Human Development Index.